Evaluation of iridociliary and lenticular elasticity using shear-wave elastography in rabbit eyes - Detorakis, Efstathios T; Drakonaki, Eleni E; Ginis, Harilaos; Karyotakis, Nikolaos; Pallikaris, Ioannis G (Acta medica (Hradec Kralove), 2014)
INTRODUCTION: A previous study has employed shear-wave ultrasound elastographic imaging to assess corneal rigidity in an ex-vivo porcine eye model. This study employs the same modality in vivo in a rabbit eye model in order to assess lens, ciliary body and total ocular rigidity changes following the instillation of atropine and pilocarpine. METHODS: Ten non-pigmented female rabbits were examined. Measurements of the lens, ciliary body and total ocular rigidity as well as lens thickness and anterior chamber depth were taken with the Aixplorer system (SuperSonic Imagine, Aix-en-Provence, France) with the SuperLinear™ SL 15-4 transducer in both eyes at baseline as well as after pilocarpine and atropine instillation. The IOP was also measured with the TonoPen tonometer. RESULTS: Changes in rigidity in the examined areas following atropine instillation were statistically not significant. Ciliary body rigidity was significantly increased whereas lens and total ocular rigidity were significantly reduced following pilocarpine instillation. The decrease in lens rigidity following pilocarpine was significantly associated with the respective increase in ciliary body rigidity. CONCLUSIONS: Shear-wave ultrasound elastography can detect in vivo rigidity changes in the anterior segment of the rabbit eye model and may potentially be applied in human eyes, providing useful clinical information on conditions in which rigidity changes play an important role, such as glaucoma, pseudoexfoliation syndrome or presbyopia.
Keywords: Ultrasonography instruments; Oxidative stress; Mydriatics; Ciliary Body; oční čočka; miotika; Ciliary body; Miotics; corpus ciliare; králíci; Lens, Crystalline; pilokarpin; pružnost; Pilocarpine; Shear-wave elastography; elastografie; Animals; atropin; ženské pohlaví; mydriatika; zvířata; Rabbits; Elasticity; Elasticity Imaging Techniques; Female; Lens; Atropine